The Evaluation of Physical Education Sport and Health during the Covid-19 Pandemic at Junior High Schools in Central Semarang Indonesia - Ariyadi, Jamal Imam; Rumini, Rumini; Priyono, Bambang (Study Program Education and Sports, Postgraduate Universitas Negeri Semarang, 2021)
The Covid-19 pandemic that is happening right now has an impact on various sectors. One of them is in the field of education, where learning in schools must be carried out online. Physical Education Sport and Health (PESH) learning is also carried out online, so it is necessary to evaluate online PESH learning. The purpose of this research is to analyze the initial state, implementation and evaluation of learning out comes include the lesson plan, learning facilities and infrastructure during the COVID-19 pandemic at Junior High Schools in Central Semarang. Researh Method evaluation using the countenance evaluation model from Stake, including antecedents, transactions, and outcomes. Collecting data used observations, and documentation. The data analysis techniques using 4 components, there are data collection, data reduction, data presentation, and concluding. The study results of all schools on Antecedent completeness of equipment, facilities and infrastructure are complete, and school program policies are appropriate. Meanwhile, all of the schools in the Transaction have not gone well, and online learning Outcomes in all schools during pandemic at Junior High Schools in Central Semarang have decreased. The conclusions from this study is that PESH in Antecedentsin online learning during Covid-19 disease at Junior High Schools in Central Semarang have complete learning tools, the program policies as needed, and support the learning process. But, on the other hand, the facilities and infrastructure are still lacking. Transaction in online learning is still constrained in its implementation, and the Outcomes have poor results because student achievement has decreased.